2016
DOI: 10.1017/s0376892915000405
|View full text |Cite
|
Sign up to set email alerts
|

Rapid conservation assessment for endangered species using habitat connectivity models

Abstract: SUMMARYTo avoid extinction of rare species in regions of active environmental change, strategic approaches are needed to manage remaining habitat. When observations of dispersal or metapopulation information are not available, habitat connectivity simulations may offer a valuable alternative source of information to assess threats and evaluate conservation options. For the Critically Endangered San Martin titi monkey (Callicebus oenanthe) in north central Peru, an updated distribution model was generated and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The UN continues to campaign to reduce the use of chemicals and minimize raw sewage volume discharges into rivers and seas. Various species threatened by extinction have lost an estimated 8% of their habitat in the last 25 years [5]. Furthermore, an additional 22% of species worldwide are at risk of facing extinction due to poaching, introducing invasive species, and climate change.…”
Section: Introductionmentioning
confidence: 99%
“…The UN continues to campaign to reduce the use of chemicals and minimize raw sewage volume discharges into rivers and seas. Various species threatened by extinction have lost an estimated 8% of their habitat in the last 25 years [5]. Furthermore, an additional 22% of species worldwide are at risk of facing extinction due to poaching, introducing invasive species, and climate change.…”
Section: Introductionmentioning
confidence: 99%
“…The spatial and temporal components of our approach may be especially useful for consideration of where and when to implement management strategies for threatened or endangered species with known habitat requirements. Habitat degradation and fragmentation are commonly cited as primary sources of species endangerment, necessitating the importance of identifying current and potential sources of habitat for threatened and endangered species (Wilcove et al 1998, Kerr and Cihlar 2004, Schaffer‐Smith et al 2016). Linden et al (2011) used a habitat potential model for Canada lynx ( Lynx canadensis ) to determine potential hare and lynx densities in the Upper Peninsula of Michigan.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing deforestation, as demand for coffee plantations, rice fields, and cattle pastures is proliferating, brought on in large part by a governmental agrarian program, has resulted in the habitat areas of Plecturocebus oenanthe to be highly fragmented (DeLuycker, 2006). Estimates suggest that already 34% of its lowland forest habitat has been lost, and that 95% of the remaining forest fragments are likely too small to support viable populations (Schaffer-Smith et al, 2016). Titi monkey habitat is affected by continued forest loss and fragmentation throughout their geographic ranges, as callicebines have averaged an 18% modification of land cover from 2000 to 2012 (Boyle 2016).…”
Section: Table IIImentioning
confidence: 99%
“…It is both geographically restricted, found only in the Río Mayo and Huallaga Central valleys, confined to ca. 14,000 km 2 of viable habitat (Schaffer-Smith et al, 2016), and altitude restricted, found ≤1200 m asl (Bóveda-Penalba et al, 2009;Shanee et al, 2011;Vermeer et al, 2011). Premontane forest or humid premontane tropical forest (Holdridge, 1967) occurs between 500 m and 1500 m altitude on the lower Amazonian slopes of the Andes and is essentially similar to the forest in Amazonian lowlands, in that they share many of the same plant genera and families (Pennington et al, 2004).…”
Section: Introductionmentioning
confidence: 99%